DRIVERS AND IMPEDIMENTS TO E-COMMERCE IN MALAYSIA - Paynter, John; Lim, Jackie (Malaysian Journal of Library and Information Science, 2001)
Online shopping was introduced to the market in the last decade as many individuals and organizations purchase through the World Wide Web. This project investigates the influence of the World Wide Web online trading on Malaysian daily life, and future trends of online shopping in Malaysia .A number of dot.com companies have been established in Malaysia and about ten thousand web sites exist in Malaysia, but only an estimated 30% are capable of providing online shopping facilities for Malaysian consumers. The focus of this paper is on the demographics of the use of online shopping in Malaysia. This study explores the development, current status and future trends of online shopping in Malaysia as well as factors that influence the decision on whether or not to use this form of commerce. Research findings include which and how often online shopping applications are used by consumers in their daily life, the benefits online shopping brings to the Malaysian communities, and factors contributing to the popularity of Internet sites.Initiatives to raise online shopping by various parties are also studied.